Paleotelmatoscopus, a proposed new genus for some fossil moth flies (Diptera, Psychodidae, Psychodinae) in Eocene Baltic amber, with description of a new species - Curler, Gregory R.; Skibińska, Kornelia (Zootaxa, 2021)
Few species of Baltic amber Psychodinae have been described to date. Some were incorrectly classified in Pericoma Walker based on an early, broad definition of the genus and holotypes were not specified. We examined approximately 50 specimens of Baltic amber Psychodinae in addition to reviewing the original series studied by Fernand Meunier. Lectotypes for Pericoma formosa Meunier and P. speciosa Meunier are designated and Paleotelmatoscopus gen. nov. is proposed to include P. formosa and P. madrizi sp. nov. Characters included in the diagnosis of this new genus and species have implications for future descriptions of Baltic amber Psychodinae. Parts of the head capsule, such as antennae, are often well-preserved and visible, and can be useful for separating species. However, these character complexes are prone to homoplasy and should not be used alone to define genera. Since it is impossible to view internal genitalic characters in fossil species, refinement of generic and species diagnoses based on external morphology is a critical factor in describing the amber fauna.